The effect of a strategy based on multiple intelligences in developing reading comprehension skills in Arabic language for ninth grade students - ALzeidaneen, Mohammad Mahmud Hwaishil (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the effect of a strategy based on multiple intelligences in developing reading comprehension skills in Arabic language for ninth grade students compared to the usual method. The sample of the study, which was chosen randomly, consisted of (75) students divided into two groups, an experimental group totaling (38) students, and a control group totaling (37) students from the ninth grade students from Abdullah II School for Excellence in the Directorate of Education in Aqaba Governorate for the academic year 2020/ 2021. To achieve the goal of the study, the researcher designed the study tools, which are: a list of reading comprehension skills, the educational program, and a test of reading comprehension skills. The results showed a statistically significant difference at the level (α = 0.05) between the two groups in favor of the experimental group that was studied using the multiple intelligences strategy. The study recommended employing a strategy based on multiple intelligences in teaching reading to primary school students.